An assessment of marine protected areas as a marine management strategy in Southeast Asia: A literature review. (1st August 2017) - Ahmad Kamil, Khairunnisa; Hailu, Atakelty; Rogers, Abbie; Pandit, Ram
Abstract: The establishment of Marine Protected Areas (MPAs) is seen as a chosen strategy in managing marine resources in Southeast Asia (SEA). The region has some of the most extensive coastline and diverse coral reef ecosystems that remain highly threatened. The need to protect these areas is definite, but establishment of a MPA often involves conflicts with its stakeholders that highly depend on the ecosystem. This paper reviews 32 studies that evaluated the MPA strategy implemented in various SEA countries since the 1980's to the present. The objective of this paper is to determine the effectiveness of the MPA strategy within the context of SEA. Biological, socioeconomic and governance indicators provided by The World Conservation Union (IUCN) were used in this paper as measures of MPA effectiveness. It was found that the MPA strategy may be ideally suited for some areas but may also be inappropriate for others. The three indicators are highly related to each other in determining a MPA success. An integrated study of these three aspects is believed to provide greater knowledge for future implementation of MPAs. Highlights: The IUCN guideline was used to assess the effectiveness of MPA strategy in SEA. Biological, socioeconomic and governance indicators are needed for comprehensive evaluation. The MPA strategy has both positive and negative impacts in SEA.